PEMIKIRAN MEWUJUDKAN GOOD UNIVERSITY GOVERNANCE (GUG) DI PERGURUAN TINGGI ISLAM - Muhammad In’am Esha (Fak. Tarbiyah UIN Maliki Malang, 2012)
This paper tries to do the reading on the challenge and at the same time try to give PTAIN offer strategic thinking respect to the steps to be done PTAIN to maintain its presence in the contemporary era. The exposure can be observed that the currently PTAIN are facing very tough challenges related to globalization. Some of the challenges face, is how to achieve Good PTAIN University Governance (GUG). As for some of important things to consider to make it happen include: management arrangements, change of paradigm, leadership, and networks collaboration.